The Power Of Jesus Christ's Teaching Methods - Lanny Laras; Daniel Tumbel (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
Learning and learning is very important in the educational process that involves teachers and students or teachers and students. Edward and Frances Simpson in their paper